Traditional horticultural knowledge change in a rural population of the Patagonian steppe - Eyssartier, Cecilia (2011)
We investigated traditional horticultural knowledge related to plant species cultivated in homegardens in an arid rural population of North-western Patagonia, Argentina. By means of semi-structured interviews and ﬁeld visits to the cultivated areas we analyzed ﬂoristic composition and structure of: vegetable-gardens, greenhouses and gardens. We evaluated species richness, cover and biogeographicalorigin in each cultivated area and analyzed the inﬂuence of socio-cultural factors, such as age and gender, on informants? cultivation practice. A total of 124 species was found: 75 species in vegetable-gardens, 63 in greenhouses and 68 in gardens. In all cultivated areas, most plant species (91%) were exotic and mainly used for edible purposes. Plant richness in homegardens increased with informants? age and both men and women play a relevant role in the maintenance of cultivated areas. Traditional knowledge in this community has been suffering an erosion process, which is in part inﬂuenced by the intervention of extension agents. However, their presence creates the possibility of integrating new and ancestral practices, favoring development of knowledge of a hybrid, syncretic nature. Alongside these changes, Pilcaniyeu inhabitants still maintain traditional homegardens cultivation, through which we can appreciate the intricate relationship between people and their physical, historical, cultural and spiritual contexts.